Does policy respond to environmental change events? An analysis of Mountain Pine Beetle outbreaks in the Western United States. Issue 90 (December 2018) - Abrams, Jesse; Huber-Stearns, Heidi; Palmerin, Marlene Luviano; Bone, Chris; Nelson, Michael F.; Bixler, R. Patrick; Moseley, Cassandra
Highlights: We searched for congressional legislation referencing mountain pine beetle. 43 relevant bills were introduced into Congress, only five became law. Two of the five laws were of substantive national importance for beetle management. Our analysis revealed trends in discourses and proposed policy solutions. Abstract: Understanding how institutions respond in the face of environmental or social shocks is a central concern in the study of the adaptive governance of social-ecological systems. This study attempted to determine whether and how the US Congress responded to epidemics of the native mountain pine beetle (MPB, Dendroctonus ponderosae ) in the federal land-dominated intermountain US West, including a ca. 2000–2010 epidemic that far outpaced any prior outbreak on record in terms of area affected. In addition, we categorized the causal narratives represented by MPB legislation and analyzed patterns over time and by political party. We found very limited evidence of specific legislative responses to MPB epidemics; of the 43 MPB-related bills introduced into Congress, only five were passed into law and of these, three had relatively limited scope or application. Our analysis of narratives shows a shift over time from bills that attempted to increase the capacity of government agencies to address MPB impacts toward bills focused on reducing or eliminating procedural and environmental analysis requirements on federal land management agencies and providing new contracting options. Our findings call into question the ability of high-level deliberative bodies to advance institutional reform to address emerging patterns of environmental change.